Comparative genome analysis of fusobacterium nucleatum - Ang, M.Y.; Dutta, A.; Wee, W.Y.; Dymock, D.; Paterson, I.C.; Choo, S.W. (Oxford University Press, 2016)
Fusobacterium nucleatum is considered to be a key oral bacterium in recruiting periodontal pathogens into subgingival dental plaque. Currently F. Nucleatum can be subdivided into five subspecies. Our previous genome analysis of F. Nucleatum W1481 (referred to hereafter asW1481), isolated from an 8-mmperiodontal pocket in a patient with chronic periodontitis, suggested the possibility of a new subspecies. To further investigate the biology and relationships of this possible subspecies with other known subspecies, we performed comparative analysis between W1481 and 35 genome sequences represented by the five known Fusobacterium subspecies.Our analyses suggest thatW1481ismost likely anew F. Nucleatum subspecies, supported by evidence fromphylogenetic analysesandmaximaluniquematchindices(MUMi). Interestingly,wefoundahorizontally transferredW1481-specificgenomicisland harboring the tripartite ATP-independent (TRAP)-like transporter genes, suggesting this bacterium might have a high-Affinity transport system for the C4-dicarboxylates malate, succinate, and fumarate.Moreover, we found virulence genes in theW1481 genome that may provide a strong defense mechanism which might enable it to colonize and survive within the host by evading immune surveillance. This comparative study provides better understanding of F. Nucleatum and the basis for future functional work on this important pathogen.